Long-term photospheric instabilities and envelopes dynamics in the post-AGB binary system 89 Herculis. Issue 1 (21st October 2020) - Gangi, M; Giarrusso, M; Munari, M; Ferrara, C; Scalia, C; Leone, F
ABSTRACT: We present a long-term optical spectroscopic study of the post-asymptotic giant branch (AGB) binary system 89 Herculis, with the aim to characterize the relationship between photospheric instabilities and dynamics in the close circumstellar environment of the system. This study is based on spectra acquired with the high-resolution Catania Astrophysical Observatory Spectropolarimeter and archive data, covering a time interval between 1978 and 2018. We find long-term changes in the radial velocity curve of the system, occurring mostly in amplitude, which correlate with the variability observed in the blueshifted absorption component of the P Cygni-like H α profile. Two possible scenarios are discussed. We also find strong splitting in the s-process elements of Ba ii 6141.713- and 6496.898-Å lines, with short-term morphological variations. A Gaussian decomposition of such profiles allows us to distinguish four shell components, two expanding and two infalling toward the central star, which are subject to the orbital motion of the system and are not affected by the long-term instabilities. Finally, we find that the numerous metal lines in emission could originate in regions of a structured circumbinary disc that have sizes proportional to the energy of the corresponding upper level transition E up . This study demonstrates the potential of long-term high-resolution spectroscopy in linking together the instability processes occurring during the late evolutionary stages of post-AGBs and the subsequent phase of PNe.